Development of influence on the formation phases of plum varieties - Sultonov Humoyun Maxmudjon ugli; Islamov Sohib Yakhshibekovich (Zien Journals, 2023)
This article examines the transition of phenological phases during the growing season of plum varieties with different sapes.
Keywords: varieties; phenological phases; methods of formation; flowering times